Correlation between metabolic syndrome disorder and circadian rhythm of physically disabled individuals - Arslan, Müge (The European Research Journal, 2018)
Objectives. The aim of this study was to examine the correlation between sleep disorder and metabolic syndrome disorder in physically disable peaple.Methods. The study was conducted among physically disabled persons who were selected from the Education and Rehabilitation Centre of Disabled People in Çorum, a city located in the central north of Turkey. Sleep quality is assessed with Turkish version of Pittsburgh Sleep Quality Index. The metabolic syndrome disorder, weight circumference and blood values of participants are examined by three health personnel from a private hospital in Çorum.Results. One hundred and three persons (56 M, 47 F) participated in this study. Metabolic syndrome disorder was found in 23 (22.3%) participants. Forty (38.8%) participants had bad sleep quality. The correlation between circadian rhythm and metabolic syndrome disorder was significantly positive (p < 0.01). It was found that the persons who have a bad sleep quality spend more energy than the persons who have good sleep quality (p = 0.001). Energy expenditure of the participants with metabolic syndrome disorder is higher than without metabolic syndrome disorder (p < 0.001) at the time of sleeping. Conclusions. This study confirms the positive relationship between circadian rhythm irregularity and metabolic syndrome disorder. Also, the study supports the idea that circadian rhythm irregularities cause an increase in daily energy expenditure which leads further metabolic syndrome disorder.